Trusting young children to help causes them to cheat less - Zhao, Li; Mao, Haiying; Harris, Paul L.; Lee, Kang (Nature human behaviour, 2024)
Trust and honesty are essential for human interactions. Philosophers since antiquity have long posited that they are causally linked. Evidence shows that honesty elicits trust from others, but little is known about the reverse: does trust lead to honesty? Here we experimentally investigated whether trusting young children to help can cause them to become more honest (total N = 328 across five studies; 168 boys; mean age, 5.94 years; s.d., 0.28 years). We observed kindergarten children’s cheating behaviour after they had been entrusted by an adult to help her with a task. Children who were trusted cheated less than children who were not trusted. Our study provides clear evidence for the causal effect of trust on honesty and contributes to understanding how social factors influence morality. This finding also points to the potential of using adult trust as an effective method to promote honesty in children.
Gesehen am 30.07.2024